The Potential for complementarity and energy generation through biomass from agricultural residues in Piauí - Nascimento de Brito, Thiago Felipe; Ferreira dos Santos Junior, Bartolomeu; Rocha Almeida, Aryfrance (Latin American Journal of Energy Research, 2023)
The Brazilian energy matrix is ​​predominantly sustained by hydroelectric generation, evidencing a considerable dependence on this source, while the energy matrix of Piauí is gradually becoming dependent on wind energy. However, there is an urgent need to promote the diversification of the energy matrix at the national level, covering different regions of the country. In this context, the exploitation of biomass as an energy source emerges as a valuable strategy to expand energy production routes. The state of Piauí stands out as a region with vast potential in various forms of energy generation, with special emphasis on the use of biomass from agricultural waste as a promising alternative.